(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In recognition of the opportunities to create economic growth and jobs and to alleviate poverty, the government has committed itself to developing the tourism sector. The 1998 document on the Tourism Policy seeks to increase employment opportunities in the tourism sector as well as to encourage economic integration by developing connections with other sectors. Therefore, the tourist development will involve not only tourist and pilgrim infrastructure but also facilitate recreation facilities, such as parks for fun, water sports, trekking, camping, safari fauna and cultural activities. 270 In addition to the four other Special Areas for Tourism (STAs) – Hyderavad, Visakhapatnam, Tirupati and Nagarjunasagar, Warangal has been added to the 1998 tourism policy by increasing from 66 to 100 Notified Tourism Areas (NTA). This is based on the 1998 Tourism Policy. Special responsibilities for infrastructure development and improvement were established by state government agencies. They have the power to obtain private finance, raise and recycle income.